TEACHING LISTENING TO YOUNG LEARNERS THROUGH SHORT ANIMATION MOVIE - Yamin, Siti Ashabul; Ratih, Koesoemo; Prastiwi, Yeny (Universitas Muhammadiyah Metro, 2023)
This research used a mixed method (explanatory sequence). This study aimed to find out the significant effect of short animation movies on the listening skills of sixth-grade students in SDIT Al-Ihsan, to know how short animation movies affect teaching listening, and to find out the students' responses and the strengths and weaknesses of using this media in teaching listening. The researcher conducted a quantitative and qualitative data analysis. Data collecting techniques were tests, questionnaires, and interviews. Meanwhile, quantitative data was analyzed with IBM SPSS Statistics 23, and qualitative data were described from interview and questionnaire analysis. The findings significantly affect the students' listening skills using short animated videos. The test hypothesis (2-tailed) indicated that the significance value of 0.001 was less than 0.005, so teaching listening using short animated films affected students' listening skills. The findings of questionnaire data and interviews supported these results. Based on the students' opinions, the short animation movie contains expressions, intonation, motion, and narration that help them easily understand the subject. According to students, the advantages of using short animated videos in teaching listening were that they were fun to watch, easy to understand, and participatory; watching short animated videos could increase student motivation; and being used as a medium for direct depiction of subject matter. According to them, the weakness of using short animated videos to learn to listen was that some pronunciations need to be faster in short animated videos. It needs to be clarified for students and make it easier for them to understand the meaning of the words they hear. The study implies that short animated movies are needed to teach listening.